Expression profiles analysis identifies specific interferon-stimulated signatures as potential diagnostic and predictive indicators of JAK2V617F+ myelofibrosis - Zhao, Yanhong; Wang, Di; Liang, Yipeng; Xu, Changlu; Shi, Lihong; Tong, Jingyuan (Frontiers in Genetics, 2022)
Objectives: This study aimed to identify specific deregulated genes with potential diagnostic and predictive values for JAK2V617F+ myelofibrosis. Methods: Two CD34+ HSPCs gene expression datasets of patients with JAK2V617F+ MPN (n = 66, including PV, ET and PMF) and healthy controls (HC) (n = 30) were acquired from GEO database. Three JAK2V617F+ MPN entities (PV, ET, PMF) were included in the study. The differentially expressed genes (DEGs) were screened between each JAK2V617F+ MPN entity and HC. Following this, functional enrichment analyses, including KEGG, Reactome, as well as GSEA, were conducted to decipher the important biological effects of DEGs. PPI network of the interested DEGs was performed to identify hub genes and significant modules. Another two gene expression profiles of patients with JAK2V617F+ MPN (n = 23, including PV, ET, SMF and PMF) and HC (n = 6) from GEO were used as external validation datasets to prove the reliability of the identified signatures above. Results: KEGG enrichment analysis revealed the DEGs of all JAK2V617F+ MPN entities were essentially enriched in inflammation and immune response signaling pathways, and the number of enriched related pathways in PMF was obviously more than that in PV and ET. Following the PPI analysis, 10 DEGs primarily related to inflammation and immune response were found upregulated in three JAK2V617F+ MPN entities. In addition, Reactome enrichment analysis indicated that interferon signaling pathways were enriched specifically in PMF but not in PV or ET. Furthermore, after the PPI analysis, several interferon (IFN)-stimulated genes were identified to be uniquely upregulated in JAK2V617F+ PMF. Analyses of gene expression patterns from external datasets validated the upregulation of several essential genes in JAK2V617F+ myelofibrosis (SMF and PMF). ROC curves indicated the four interferon-related genes (OAS1, IFITM3, GBP1, GBP2) have high AUC values when distinguishing JAK2V617F+ myelofibrosis from PV or ET. Conclusion: Four interferon-stimulated genes (OAS1, IFITM3, GBP1, GBP2) exclusively upregulated in JAK2V617F+ myelofibrosis could be considered as candidate molecular diagnostic biomarkers, predictive indicators of myelofibrosis progression as well as potential treatment targets in myelofibrosis.